k KREATIVITAS MAHASISWA BERBASIS KEARIFAN LOKAL KALIMANTAN SELATAN: STUDI EKSPERIMENTAL PENERAPAN MODEL PROJEK BASED LEARNING (P-BL): kreativitas mahasiswa - Arina Wulandari; Wulida Makhtuna (UNIB Press, 2024)
This research aims to determine the ability of PGSD students to develop their skills and creativity, especially those containing the local wisdom of South Kalimantan. The type of research is experimental time-series research. The subjects in the research were 70 students from PGSD students who were taking Skills and Crafts Education courses in Elementary School from two different classes and the same semester. The data used was taken from the results of students' activities in the process of producing products for one semester, using the P-BL model. However, the data displayed is taken from the last two products of each class. Data were collected using the time series experimental method. From the results obtained was showed that the creativity of PGSD students, especially in terms of innovation, was still very far from the criteria that could be said to be good. Because judging from the existing results, the average innovation score is still below the criteria, but looking from assessment 1 to assessment 2 there has been an increase in the score but it is still below the good criteria. Meanwhile, the value of local wisdom has seen quite a good improvement. Therefore, it can be concluded that the use of the PjBL model in elementary education and crafts courses is said to be successful, but it cannot yet be said to have the maximum level of success.